2009
DOI: 10.1103/physrevb.79.220514
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of electron correlations inLixCoO2(x=0.0

Abstract: CoO2 is the parent compound for the superconductor NaxCoO2·1.3H2O and was widely believed to be a Mott insulator. We performed 59 Co nuclear magnetic resonance (NMR) and nuclear quadrupole resonance (NQR) studies on LixCoO2 (x = 0.35, 0.25, 0.12, and 0.0) to uncover the electronic state and spin correlations in this series of compounds which was recently obtained through electrochemical de-intercalation of Li from pristine LiCoO2. We find that although the antiferromagnetic spin correlations systematically inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
5
16
2
Order By: Relevance
“…Our evaluation of the correlation strength : 15.6, clearly situates the CoO 2 compound very close to the Mott transition. Similarly, our results are in agreement with NMR measurements 8,10 that sees an increase of the antiferromagnetic coupling with decreasing sodium content. However, contrarily to Kawasaki et al 10 we do not find the pure CoO 2 compound behaving on a specific way.…”
Section: Discussionsupporting
confidence: 92%
“…Our evaluation of the correlation strength : 15.6, clearly situates the CoO 2 compound very close to the Mott transition. Similarly, our results are in agreement with NMR measurements 8,10 that sees an increase of the antiferromagnetic coupling with decreasing sodium content. However, contrarily to Kawasaki et al 10 we do not find the pure CoO 2 compound behaving on a specific way.…”
Section: Discussionsupporting
confidence: 92%
“…Based on dc-magneticsusceptibility data, combined with results of 59 Co-NMR/ NQR observations, 16 the electronic phase diagram of Li x CoO 2 was established. It was found that the phase diagram of Li x CoO 2 is complex and the electronic properties are sensitively influenced by the Li content ͑x͒.…”
Section: Discussionmentioning
confidence: 99%
“…19 Recently, we performed 59 Co-NMR/ NQR observations on CoO 2 ͑x = 0.0͒ and Li x CoO 2 ͑x = 0.12-0.35͒. 16 Our 59 Co-NMR/ NQR studies revealed a complex nature in the electronic phase diagram in the low Li content regime. It was found that antiferromagnetic-like fluctuations develop and a crossover to a Fermi-liquid regime occurs below a characteristic temperature T ‫ء‬ , when the Li content is smaller than x = 0.35.…”
Section: A Electronic Phase Diagram Of the LI X Coo 2 Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Recently, we successfully obtained a sample series of single-phase Li x CoO 2 through electrochemical deintercalation of Li from pure LiCoO 2 (x = 1.0) bulks. 17,18 Based on dc-magnetic-susceptibility data, combined with results of 59 Co nuclear magnetic resonance (NMR) and nuclear quadrupole resonance (NQR) observations, 19 the electronic phase diagram of Li x CoO 2 was established. 20 The phase diagram of Li x CoO 2 is complex and the electronic properties are sensitively influenced by the Li content (x).…”
Section: Introductionmentioning
confidence: 99%